PRODUCTION COST ANALYSIS AND RETURNS ON AUNT RABE’S BASKET-NECK SHIRT, KOSAMPHI DISTRICT, KAMPHAENG PHET PROVINCE - Promraksa, Eakwiniti; Wongkongkaew, Pimpaka; Wongkongkaew, Benyapha (Journal of MCU Nakhondhat, 2025)
This research is a qualitative study aimed at 1) Analyzing the costs and returns from producing collarless shirts at Aunt Rabieb's shop, 2) Determining the selling price and planning appropriate profits from producing collarless shirts at Aunt Rabieb's shop, and 3) Studying the problems, obstacles, and suggestions from the production and sale of collarless shirts at Aunt Rabieb's shop. A purposive sample of 6 people was selected, including 1 entrepreneur and 5 producers from Aunt Rabieb's collarless shirt shop. The research tool used was in-depth interviews. Descriptive data analysis was conducted. The research findings revealed that the original selling price was 120 baht per shirt, with a profit of 59.17 baht. The production costs included direct materials at 45 baht, direct labor at 5 baht, and production expenses at 10.83 baht. The returns showed a profit of 59.17 baht per shirt, with an income of 5,760 baht and a profit of 2,840.16 baht per month. However, the shop still had operational expenses, including transportation and fuel costs of about 1,000 baht or approximately 20.83 baht per shirt, resulting in a remaining profit of 38.34 baht, which is 63.03% of the total cost. This profit from sales did not meet expectations. The researcher proposed a new selling price of 140 baht per shirt to achieve a profit of 60 baht per shirt, selling a total of 48 shirts, resulting in an income of 6,720 baht and a profit of 2,920 baht, which is the desired profit. Additionally, there were issues related to the rising prices of raw materials, insufficient labor and production equipment when increasing production, and the need to enhance skills to maintain the beauty of the shirt colors and fabrics.